In-stope pillar scaling and fracturing in Southern African deep level gold mines: 26th International Symposium on Mine Planning and Equipment Selection (MPES2017). 29 – 31 August 2017, Luleå, Sweden. - Zvarivadza, T; Sengani, F.; Adoko, A.C. (2022)
Pillar support is the most common natural support system which is applied in most of the deep to utra-deep gold mines, as a way of preventing the fall of ground and maintain the stability of the rock mass. Deep level gold mines are currently operating at a depth of 2.7km to 4km from the ground surface with the use of rectangular yield pillars, 6m wide, 15m long and 5.5m high. In-stope pillar fracturing and scaling is one of the common problems faced at deep level gold mines. This paper investigates the general and technical behavior of the in-stope pillar, taking into consideration; fracture frequencies within the in-stope pillar, scaling of the in- stope pillar, behavior of the in-stope pillar under different micro seismic events and ground closure at the back areas and closer to the stope faces. The investigation involves the analyses of in- stope pillar fracturing, scaling and ground closure through the use of underground monitoring instrumentation which includes; borehole camera, extensometer, Electronic Monitoring Cable Anchor Device (EMCD), Falls of Ground Light (FOG light) and closure meters. Abaqus Explicit software was used to calculate the ground closure and 1 along the boundaries of the in-stope pillar. The results of the borehole camera indicated that most of the in-stope pillars were adequately fractured to the core, but the scaling of the pillar was found to be extensive in the back area (30m and above, from the face), while occurring gradually towards the face (10m and less to the face). The closure monitoring systems indicated ground closure ranging from 10mm to 500mm. Based on the results calculated by the model, the ground closure were found to range from 300mm to 600mm. 1 was found to range from 270MPa to 400MPa. The work presented in this paper is part of a Masters of Science in Mining Engineering by research at the University of Witwatersrand Johannesburg, School of Mining Engineering.